Phytophagous mites associated to fragaria spp., advances in pest management in South America - Vásquez, Carlos; Colmenárez, Yelitza [UNESP]; Dávila, Marta; Pérez, Marco; Zurita, Hernán; Telechana, Norma (Science Alert, 2016)
Background and Objective: Phytophagous mites are considered key pests in strawberry worldwide however, there is a lack of information about the economic impact in South America. Understanding factors that affect the mite population establishment are crucial for design and success of a pest management program. A revision of the most valuable studies related to phytophagous mites associated to strawberry was made with special emphasis in South America. Besides, a structured questionnaire was used to assess pesticide knowledge, attitudes and practices among strawberry growers in some municipalities from the Province of Tungurahua. According to the review, most of the information about the impact and control of these mite species has been yielded in Europe and North America. In South America, the most information has been yielded in Brazil making this a fact that more studies are required from other South American countries such as Ecuador. According to the answers, farmers are able to recognize symptoms of mite feeding. They agreed that the only method known by them for pest control is using pesticides. Consequently, they neglect other strategies such as biological control, plant resistance or botanical pesticides. Conclusion: As strawberry exploitation was initiated in Tungurahua damage by phytophagous mites was evident and subsequent difficulties in the management of pest populations tended to increase due to mistakes in selection and application of acaricides. Despite this, there is no available information about pest mite management in Ecuador. Thus, this review aims to contribute to establish the basis for designing management sustainable programs available for Ecuadorian strawberry growers.
Keywords: Ecuador; Management; Pest mites; Strawberry